Info Note: Strengthening Food Systems Transformation in East and Southern Africa: Leveraging Science Driven Business Acceleration to Catalyse Private Sector Finance - Zulu-Hume, Mercy F.; Musau, C.; Ng'ang'a, Salome; Njiru, AnnRita; Dahl, Hauke; Sewe, L. (2023)
• Agriculture in Africa has untapped potential to meet regional and global food demands, but it faces challenges like fragmentation, inefficient value chains, and climate shocks. Transforming food systems will come at a cost. • There is an opportunity to harness business acceleration as a catalyst for private sector financing food systems transformation, and a powerful scaling mechanism for climate-smart agriculture (CSA). • Science and research have a role to play in business acceleration to support the adoption and strengthening of CSA practices, benefiting both agribusiness performance and smallholder farmers. • Combining tailored CSA technical assistance with investment readiness in an integrated approach holds significant potential for driving regional food systems transformation because it ensures that agribusinesses not only have access to the necessary knowledge and expertise but are also well-prepared to secure the financial resources required for implementing sustainable and climate-smart solutions. • Selecting appropriate funding partners and mechanisms, acquiring investment knowledge, nurturing relationships with capital providers, and showcasing social and environmental impact are vital for successful financing in the agriculture sector.